New Directions in Geometric and Applied Knot Theory - Reiter, Philipp; Blatt, Simon; Schikorra, Armin (De Gruyter, 2022)
The aim of this book is to present recent results in both theoretical and applied knot theory-which are at the same time stimulating for leading researchers in the ﬁeld as well as accessible to non-experts. The book comprises recent research results while covering a wide range of diﬀerent sub-disciplines, such as the young ﬁeld of geometric knot theory, combinatorial knot theory, as well as applications in microbiology and theoretical physics.